Analisis Yuridis terhadap Pertimbangan Hakim dalam Menjatuhkan Putusan Bebas (Vrijspraak) pada Perkara Korupsi Penyalahgunaan Wewenang (RechtJiva, 2025)
This research aims to examine the judges' considerations in acquittal (vrijspraak) in corruption cases involving abuse of authority, focusing on Decision No. 6059K/Pid.Sus/2023. The research method used is empirical research, with primary data obtained through interviews with judges, as well as secondary and tertiary data derived from articles, books, and relevant legislation. The results show that the judicial process in this case includes investigation, prosecution, and trial stages based on the principles of justice and legal certainty. The judge rejected the public prosecutor's charges because the evidence presented did not meet the standard of valid and convincing proof. The defendant, as the Head of BRI Gorontalo Branch Unit, was found to lack the authority to approve loans above Rp100,000,000.00, and there was no evidence of involvement in document forgery or credit fund misuse. The judge decided to acquit the defendant based on the presumption of innocence and restored the defendant's rights in accordance with Article 191 Paragraph (1) of the Criminal Procedure Code (KUHAP) and Law No. 46 of 2009. Furthermore, the ratio decidendi of the Supreme Court's decision reflects the principles of justice, legal certainty, human rights protection, and the presumption of innocence. The Supreme Court affirmed that the first-instance court had correctly applied the law and there was no reason to overturn the decision. The implications of this decision demonstrate consistency in the application of the law, restore the defendant's rights, and set an important precedent in the Indonesian criminal justice system, particularly in corruption cases.